2023
DOI: 10.1186/s12879-023-08359-w
|View full text |Cite
|
Sign up to set email alerts
|

Treatment persistence of bictegravir/emtricitabine/tenofovir alafenamide and efavirenz + lamivudine + tenofovir disoproxil among HIV-1 patients newly starting treatment in Hunan Province in China

Abstract: Background Though bictegravir/emtricitabine/tenofovir (BIC/FTC/TAF) have been regulatory approved and included in the National Reimbursement Drug List in China, due to the affordability concern, generic version of efavirenz + lamivudine + tenofovir (EFV + 3TC + TDF) is still recommended as the first-line therapy in the clinical guideline and widely used in clinical practice. The aim of the study is to assess the persistence with first-line BIC/TAF/TAF and EFV + 3TC + TDF in newly treated HIV-1 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…So far, several observational studies have compared the clinical outcomes between TLE and DTG + 3TC or TLE and B/F/TAF in treatment-nave individuals, respectively, and all have consistently showed that either DTG + 3TC or B/F/TAF was superior to TLE in terms of rapid decline in VL or regimen persistence. [1416] However, we still lack comparative data in regard to efficacy and safety of DTG + 3TC and B/F/TAF in ART-nave individuals in a real-life scenario. Therefore, we conducted this study to fill this knowledge gap.…”
Section: Discussionmentioning
confidence: 99%
“…So far, several observational studies have compared the clinical outcomes between TLE and DTG + 3TC or TLE and B/F/TAF in treatment-nave individuals, respectively, and all have consistently showed that either DTG + 3TC or B/F/TAF was superior to TLE in terms of rapid decline in VL or regimen persistence. [1416] However, we still lack comparative data in regard to efficacy and safety of DTG + 3TC and B/F/TAF in ART-nave individuals in a real-life scenario. Therefore, we conducted this study to fill this knowledge gap.…”
Section: Discussionmentioning
confidence: 99%